2021
DOI: 10.1161/jaha.119.014572
|View full text |Cite
|
Sign up to set email alerts
|

MEDI6012: Recombinant Human Lecithin Cholesterol Acyltransferase, High‐Density Lipoprotein, and Low‐Density Lipoprotein Receptor–Mediated Reverse Cholesterol Transport

Abstract: Background MEDI6012 is recombinant human lecithin cholesterol acyltransferase, the rate‐limiting enzyme in reverse cholesterol transport. Infusions of lecithin cholesterol acyltransferase have the potential to enhance reverse cholesterol transport and benefit patients with coronary heart disease. The purpose of this study was to test the safety, pharmacokinetic, and pharmacodynamic profile of MEDI6012. Methods and Results This phase 2a double‐blind stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 44 publications
1
14
0
Order By: Relevance
“…In the clinical trial, it was proved that ACP-501 infusion rapidly decreased small- and intermediate-sized HDL, whereas large HDL increased and it was thought well in terms of safety and tolerability in their test results ( Shamburek et al, 2016 ). Besides, another more active rhLCAT ( George et al, 2021 ), MEDI6012, was reported not only reverses HDL dysfunction in ACS patients caused by LCAT concentration/activity but also results in greater HDL function in a 2019 clinical trial ( Ossoli et al, 2019 ). Certainly, intense effort has been focused on developing ways to make a durable and stable plasma LCAT concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical trial, it was proved that ACP-501 infusion rapidly decreased small- and intermediate-sized HDL, whereas large HDL increased and it was thought well in terms of safety and tolerability in their test results ( Shamburek et al, 2016 ). Besides, another more active rhLCAT ( George et al, 2021 ), MEDI6012, was reported not only reverses HDL dysfunction in ACS patients caused by LCAT concentration/activity but also results in greater HDL function in a 2019 clinical trial ( Ossoli et al, 2019 ). Certainly, intense effort has been focused on developing ways to make a durable and stable plasma LCAT concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, among the mainly enriched 13 cellular components, some of them were involved in cellular material transport (transmembrane transporter complex, transporter complex). The transport of substances by macrophages is also critical in the development of inflammation [ 27–29 ]. For example, members of the ABC transporter superfamily, ABCA1 and ABCG1, facilitate cholesterol efflux from foam cells to the extracellular cholesterol receptors Apolipoprotein AI (ApoA-I) and high density lipoprotein (HDL), respectively, restricting foam cell development and slowing the progression of atherosclerosis [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given that, administration of recombinant LCAT may lead to increased cholesterol esterification and enhanced RCT. Although some animal studies suggest that the overexpression of LCAT does not result in enhanced RCT [ 239 , 515 ], in clinical trials in patients with CHD, administration of the recombinant LCAT (ACP-501, another name MEDI6012) increased HDLc, favourably altered HDL metabolism, increased the apoA-I levels, CEC and raised the number of large HDL particles whilst small and intermediate-size HDL particles along with proatherogenic LDL particles decreased [ 516 , 517 ]. Many small-molecule LCAT activators , such as DS-8190a, have been successfully tested for the reduction in atherosclerotic lesions in animal models [ 518 ].…”
Section: Currently Available Hdl-targeted Therapiesmentioning
confidence: 99%